Wybrane zagadnienia dotyczące problematyki czynności prawnych dokonywanych przez osoby prawne Kościoła katolickiego - Głowacka, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The elaboration includes a comparison of the regulations of canon law and national law. It constitutes an attempt at answering the question whether the internal law of the church is part of the law currently binding in Poland. The article also discusses the problem of effectiveness of acts in law by legal persons of the Catholic Church. The issue aroused the interest a decade ago when it was analysed by the Supreme Court. The doctrine still has not developed a coherent approach to the location of the Code of Canon Law in the order of universally binding law.
Keywords: skuteczność czynności prawnych; osoby prawne kościoła katolickiego; prawo wewnętrzne; system prawa powszechnie obowiązującego w Polsce; Kodeks Prawa Kanonicznego